2021
DOI: 10.3390/jcm10204641
|View full text |Cite
|
Sign up to set email alerts
|

Troglitazone-Induced PRODH/POX-Dependent Apoptosis Occurs in the Absence of Estradiol or ERβ in ER-Negative Breast Cancer Cells

Abstract: The impact of estradiol on troglitazone (TGZ)-induced proline dehydrogenase/proline oxidase (PRODH/POX)-dependent apoptosis was studied in wild-type and PRODH/POX-silenced estrogen receptor (ER) dependent MCF-7 cells and ER-independent MDA-MB-231 cells. DNA and collagen biosynthesis were determined by radiometric method, prolidase activity evaluated by colorimetric method, ROS production was measured by fluorescence assay. Protein expression was determined by Western blot and proline concentration by LC/MS ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 57 publications
(99 reference statements)
0
5
0
Order By: Relevance
“…These receptors can be activated by natural ligands, such as fatty acids or prostaglandins, as well as by synthetic ligands [20][21][22][23]. The most popular and well-studied synthetic ligands of PPARγ are thiazolidinediones (i.e., troglitazone, pioglitazone), the class of drugs used for the treatment of type 2 diabetes mellitus [24][25][26]. Interestingly, they were found to provoke proapoptotic activities in cancer cells [25,27].…”
Section: Introductionmentioning
confidence: 99%
“…These receptors can be activated by natural ligands, such as fatty acids or prostaglandins, as well as by synthetic ligands [20][21][22][23]. The most popular and well-studied synthetic ligands of PPARγ are thiazolidinediones (i.e., troglitazone, pioglitazone), the class of drugs used for the treatment of type 2 diabetes mellitus [24][25][26]. Interestingly, they were found to provoke proapoptotic activities in cancer cells [25,27].…”
Section: Introductionmentioning
confidence: 99%
“…Glycolysis is also induced by oncogenes activation and loss of tumor suppressors, linking a high rate of glucose metabolism and cancer [ 8 ]. Since glucose is supporting cancer progression, it has been suggested that controlled calorie intake will reduce oxidative stress and protect cells from becoming oncogenic [ 9 ]. Therefore, caloric restriction could ameliorate the risk factors in breast cancer by reducing blood glucose levels, inflammation, and the onset of angiogenesis [ 10 ].…”
mentioning
confidence: 99%
“…A similar effect was found in MCF-7 cells treated with non-steroidal anti-inflammatory drugs ( Kazberuk et al, 2022b ). Other studies on MCF-7 and MDA-MB-231 cells highlighted the role of estrogens and estrogen receptors (ERα and ERβ) in PRODH/POX-dependent apoptosis ( Lewoniewska et al, 2021 ). We have found that the activation of PRODH/POX (by troglitazone) induced apoptosis only in the absence of estradiol or ERβ in MDA-MB-231 cells.…”
Section: Discussionmentioning
confidence: 99%